STRATAL PRODUCED WATER IN OIL FIELDS AS HYDROMINERAL RAW MATERIAL - Chomko, D.; Reva, M.; Dyniak, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The purpose of this paper is to investigate the possibility of produced water use in oil fields for further development as hydromineral raw material for the extraction of valuable components. The article determines the relevance of the issue of produced water extraction in oil fields of the Eastern oil and gas region of Ukraine (DnieperDonetsk depression). Close attention is paid to the negative environmental and economic impacts that may be caused by produced water. The method of disposal of this water as hydromineral raw material for industry is also described. The successful commercial experience of using this method is given in the paper. This method can significantly reduce the oil production cost and increase the resource base of the country. The authors determined the basic chemical elements and compounds which are potential for mining and also indicated their price at international markets. They are: bromine, iodine, boron, lithium, strontium and certain salts. The example of produced water recourse estimation of the Absheron peninsula oilfield as hydromineral raw material and possible income from extraction of components is shown in the paper. The article analyses produced water of four oil fields of Ukraine based on commercially cost-effective concentrations of chemicals potential for mining. The components potential for mining at studied deposits were determined as follows: boron, strontium, potassium and magnesium at Kachanivske and Rybalske deposits; sodium chloride, magnesium, iodine and boron at Chutivske deposits. The concentration of chemicals was determined as the main criterion when estimating this kind of resources. Quantitative estimation of groundwater is very hard to conduct because of outdated regulations applied to chemical analyses of reduced water. Chemical analyzes are conducted only at regulated rates that do not show the majority of dissolved components and chemical compounds. The method of use of reduced water as hydromineral raw material is very promising direction for the industry of Ukraine, which can give the second life to exhausted oil fields but as industrial water deposits.
Keywords: produced water; oil field; hydromineral raw material